2011
DOI: 10.1159/000334543
|View full text |Cite
|
Sign up to set email alerts
|

Does Colorectal Cancer in Ulcerative Colitis Patients Constitute a Risk for Chemotherapy Refractoriness? A Systemic Approach by Detailed Analysis via the Electronic Tumor Base Documentation System

Abstract: Background: Ulcerative colitis (UC) patients may develop colorectal cancer (CRC), especially with pancolitis and longer UC duration. The question whether CRC with underlying UC has a dismal prognosis remains unsettled. Patients and Methods: We performed an electronic tumor base documentation (eTBD) search of CRC and UC patients at our department to address whether (1) CRC prognosis is impaired and (2) defined risks can be determined. Results: With the inclusion of an index patient with UC and unresponsive CRC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[42] have reported that colon cancer following ulcerative colitis hasasimilaroverallsurvivalasregularCRC,buthasaworse response to chemotherapy, suggesting enhanced resistance or enhanced proportion of CSCs. Studies investigating the statusofCSCsatdifferentstagesofUCarescanty.However, asstatedabove,studiesbyCarpentinoetal.…”
mentioning
confidence: 99%
“…[42] have reported that colon cancer following ulcerative colitis hasasimilaroverallsurvivalasregularCRC,buthasaworse response to chemotherapy, suggesting enhanced resistance or enhanced proportion of CSCs. Studies investigating the statusofCSCsatdifferentstagesofUCarescanty.However, asstatedabove,studiesbyCarpentinoetal.…”
mentioning
confidence: 99%